Synthesis, characterisation and anti-corrosion screening of Ni(ii) n-methylcyclohexyldithiocarbamate and n-ethylcyclohexyldithiocarbamate complexes / Siti Raubbah Mohd Zamri - Mohd Zamri, Siti Raubbah (Faculty of Applied Sciences, 2017)
Dithiocarbamate is a ligand that can act as a corrosion inhibitors due to the presence of sulphur and nitrogen atom. Ni(II) N-methylcyclohexyldithiocarbamate, Ni[MeCycHexdtc]2 and Ni(II) N-ethylcyclohexyldithiocarbamates, Ni[EtCycHexdtc]2 complexes were synthesised through one-pot synthetic method at room temperature and have been characterised by using elemental analyser (CHNS), fourier transform infrared-attenuated total reflectance (FTIR-ATR) spectroscopy, Ultraviolet-Visible (UV-Vis) spectroscopy, nuclear magnetic resonance (NMR) and molar conductivity. The stretching frequency of thioureide band, ν(C−⃛N) appeared at 1497 cm-1 for Ni[MeCycHexdtc]2 and 1484 cm-1 for Ni[EtCycHexdtc]2 while the stretching frequency of ν(C=S) has shifted to lower wavenumber as it changes from double bonding to partial bonding, ν(C−⃛S) at (1000±70 cm-1) when compared with the raw material. The structures of both complexes were confirmed as the calculated of percentage for carbon, hydrogen, nitrogen and sulphur were similarly as the results by the elemental analyser. Meanwhile, the percentage of the metal of the complexes are carried by gravimetric analysis which is 12.8% (Ni[MeCycHexdtc]2) and 12.25% (Ni[EtCycHexdtc]2). This was supported by the result from 1H NMR and 13C NMR with the amount of the hydrogen and carbon in the symmetry of complexes. The Ni[MeCycHexdtc]2 complex indicated the square planar complex but not for Ni[EtCycHexdtc]2 complex where it shows the tetrahedral complex. There also a new absorption peak appeared at range 400-600 nm for UV-Vis spectra which show the presence of d-d transition and proved that the complexes were successfully formed. The corrosion inhibition was determined by weight loss method which also give the percentage of inhibition efficiency. Based on the experiment, the mass loss will decrease when the concentration of the complexes were increased. Thus, percentage of efficiency will also increase.